From «School Buildings» to «School Architecture» – School Technicians, Grand School Buildings and Educational Architecture in Prussia and the USA in the Nineteenth Century - Töpper, Daniel; Isensee, Fanny (Historia y Memoria de la Educación, 2020)
The history of school buildings is commonly written as a history of architecture, focusing on outstanding architects and buildings. However, the connection between pedagogical-administrative prescriptions and educational architecture has been studied less, particularly in the nineteenth century. This article highlights the often-overlooked agency of school technicians and proposes to interpret the nineteenth-century history of building schools as a history of implementing pedagogical-administrative objectives. The design of schools followed the inner differentiation of school curricula, at the same time being affected by the growth of school sizes prompted by school management structures and their efficiency aims. We will show how in larger cities the initial one-classroom schools developed into multiple-classroom buildings, taking on their final form in “grand school buildings”. The organizational developments tried and tested here would later become the national standard, with rural schools following with a certain delay. In order to grasp the emergence of the phenomena of these “grand school buildings” we combine the Prussian and US-American cases in their transatlantic connection in order to comprehend the transnational dimension of school building norms. Being closely connected through mutual observation, the US and Prussian contexts established two decisive aspects: in the Prussian case, the division into separate classrooms as functional units of school construction was implemented, while in the United States additional school rooms such as the assembly hall and specific subject-related rooms were introduced. “Grand school buildings” initiated the interest of the architectural profession, leading to negotiations between school technicians and architects.